Recommendations for management of infants and young children with achondroplasia: Does clinical practice align? - Guillen-Navarro, Encarna; AlSayed, Moeenaldeen; Alves, Inês; Ben-Omran, Tawfeg; Boero, Silvio; Cormier-Daire, Valérie; Fauroux, Brigitte; Fredwall, Svein; Irving, Melita; Kunkel, Philip Oskar Sean; Lampe, Christian Gerhard; Lausch, Ekkehart; et al. (Orphanet journal of rare diseases, 2025)
Achondroplasia is one of the most prevalent forms of skeletal dysplasia. Lifelong follow-up by an experienced multidisciplinary team is required, particularly during the first 2 years. In 2021, international consensus recommendations and guiding principles were published by two groups.
Gesehen am 16.07.2025